2003
DOI: 10.1089/108729103322231268
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Self-Reported Questionnaire Assessing Adherence to Antiretroviral Medication

Abstract: The aim of this study was to verify the validity of a new self-reported questionnaire designed to assess nonadherence to antiretroviral medication among patients with HIV. Two hundred fifty-six patients from four clinics participated in a prospective longitudinal study. The questionnaire was designed to measure if patients with HIV were taking less than the total number of antiretroviral pills prescribed by their physician. Change in viral load was used as the criterion for validity analyses. Self-reported adh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 15 publications
1
46
1
2
Order By: Relevance
“…"; 3) "Did you miss your antiretroviral dose three days ago?". These questions were adopted from a tool developed and validated by Gagne & Naccache [19]. Respondents were asked to indicate by Yes or No whether on any of the past three days they had missed their morning/lunch or evening/dinner doses (for those not yet on fixed dose combinations) or their daily dose (for those on fixed dose combinations).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…"; 3) "Did you miss your antiretroviral dose three days ago?". These questions were adopted from a tool developed and validated by Gagne & Naccache [19]. Respondents were asked to indicate by Yes or No whether on any of the past three days they had missed their morning/lunch or evening/dinner doses (for those not yet on fixed dose combinations) or their daily dose (for those on fixed dose combinations).…”
Section: Methodsmentioning
confidence: 99%
“…A few additional questions were developed to enlist responses peculiar to this study. The questionnaire included questions on: respondents' socio-demographic data (adopted from ORC Macro); PLHIV support group participation (developed by the researchers); and adherence to ART (adopted from a previously validated tool [19].…”
Section: Data Collectionmentioning
confidence: 99%
“…On the other hand, some studies use measurements pertaining to 3 or 4 days before the questionnaire, 10,15,16 although we considered that it was easier for the patient to remember 7 days, which is one week, rather than 4. Moreover, because some studies had shown good results with these three time settings, 17 the decision was finally taken to use these three measurements.…”
Section: Medical and Psychological Assessmentmentioning
confidence: 99%
“…Most of these adherence scales measure the number of doses taken 12,42,181,[184][185][186]189,195,196,199,206,208 and contain items such as "how many days over the past month did you take less than prescribed? 181 " and "did you miss a tablet yesterday?…”
Section: Content Of the Scalesmentioning
confidence: 99%
“…12,53,55,60,156,187,[189][190][191][192]194,195,[197][198][199]208,210 The Medicines Adherence Questionnaire (MAQ), which is a simple 4-item questionnaire, has been validated in a broad range of diseases, including hypertension, dyslipidaemia, heart failure and Parkinson's disease. 18,37,293,294 Figure 2.2 Disease populations used to validate self-report adherence scales…”
Section: Content Of the Scalesmentioning
confidence: 99%